The Multivariable H-function and M-series involving the generalized Mellin-Barnes contour integral swith general class of polynomials (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In this research paper, we will study some important integral formulas, with the help of whichthey play a major role in the study of the hypergeometric functions and multivariable Hfunction.In this study we will use these formulas to get the solutions of M-series and generalclass of polynomials in the form of multivariable H-function. The results proved in generalforms and besides of this have been put in a compact from avoiding the occurrence of infiniteseries and thus making them useful in applications. In this research paper we can obtain newand some modified known results which will brings new ideas and fact in field ofhypergeometric and polynomials studies.